2023
DOI: 10.1038/s41598-023-28295-8
|View full text |Cite
|
Sign up to set email alerts
|

Post-vaccination serum cytokines levels correlate with breakthrough influenza infections

Abstract: Post-vaccination cytokine levels from 256 young adults who subsequently suffered breakthrough influenza infections were compared with matched controls. Modulation within the immune system is important for eliciting a protective response, and the optimal response differs according to vaccine formulation and delivery. For both inactivated influenza vaccine (IIV) and live attenuated influenza vaccines (LAIV) lower levels of IL-8 were observed in post-vaccination sera. Post-vaccination antibody levels were higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Our findings on trained immunity were similar to previous studies that attenuated live BCG vaccines induced enhanced AP-1 loci 13 and inactivated SARS-CoV-2 vaccine induced relevant gene expression changes 60 . Those were contrast to reduction in the accessibility of AP-1 binding sites and production of innate cytokines with seasonal inactivated influenza vaccines 22,61 . A previous study has also reported the presence of an immune refractoriness state in a specific monocytes celltype following vaccination with the BNT162b2 mRNA vaccine 8 .…”
Section: Discussionmentioning
confidence: 98%
“…Our findings on trained immunity were similar to previous studies that attenuated live BCG vaccines induced enhanced AP-1 loci 13 and inactivated SARS-CoV-2 vaccine induced relevant gene expression changes 60 . Those were contrast to reduction in the accessibility of AP-1 binding sites and production of innate cytokines with seasonal inactivated influenza vaccines 22,61 . A previous study has also reported the presence of an immune refractoriness state in a specific monocytes celltype following vaccination with the BNT162b2 mRNA vaccine 8 .…”
Section: Discussionmentioning
confidence: 98%
“…Previous research had revealed an increase in IP-10 levels after vaccinations ( Tang et al., 2023 ), and the increase was evident in healthy individuals as well as in elderly or cancer patients after administration of the BNT162b2 vaccine ( Konnova et al., 2022 ). According to the literature, after receiving a second vaccine dose, a memory response was induced, leading to a significant increase in levels of IFN-g, IP-10/CXCL10, IL-6, and TNF-a that were crucial for quickly recruiting and activating effector immune cells ( Bergamaschi et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our opinion, it might be more evident in vaccines that activate the immune system as their primary mechanism. A rise in the number of these cytokines has been observed post-vaccination when using such vaccines as influenza and COVID-19 and might be more evident in subjects who have already had contact with either virus or their first dose of a vaccine [27,28]. With the ongoing high COVID-19 transmission in 2022, it was difficult to evaluate individuals' exposure [29].…”
Section: Discussionmentioning
confidence: 99%